NH4MSO4F (M = Mn, Fe, Co, Ni): A series of thermally stable transition metal fluorosulfates with KTP-type structure. (15th September 2018) - Ge, Gen-wu; Luo, Wen; Zhang, Xin-lei; Du, Xiao-di; Liang, Li-li
Graphical abstract: New series of transitional metal fluorosulfates NH4 MSO4 F was solvothermally synthesized in the presence of HF from the solvent of DMA. The 3D framework is constructed from 2D layered sheets made by two kinds of [MO4 F2 ] n chains and SO4 tetrahedra. These compounds show thermal stability and antiferromagnetism. Abstract: Four new transition metal fluorosulfates NH4 MSO4 F (M = Mn, 1 ; Fe, 2 ; Co, 3 ; Ni, 4 ) were solvothermally synthesized in the solvent of N, N-dimethylacetamide (DMA) with HF as the mineralization agent. The X-ray single crystal diffraction analyses revealed that 1 –4 are isomorphous, and possess a three-dimensional framework with the same structural topology as the known nonlinear optical material KTiOPO4 (KTP). The four compounds were constructed from MO4 F2 octahedra and SO4 tetrahedra to form two kinds of intersecting 6-membered ring channels along the a and c axes, respectively. Within the channels locate the NH 4 + cations from the decomposition of DMA molecules. All the compounds are thermally stable up to 330 °C. The magnetic studies of 1 –4 revealed the antiferromagnetic interaction behaviors in the range of 1.8–300 K.